2013
DOI: 10.1002/cncr.28254
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐222 and MicroRNA‐146b are tissue and circulating biomarkers of recurrent papillary thyroid cancer

Abstract: BACKGROUND: Papillary thyroid cancer (PTC) persistence or recurrence and the need for long-term surveillance can cause significant inconvenience and morbidity in patients. Currently, recurrence risk stratification is accomplished by using clinicopathologic factors, and serum thyroglobulin is the only commercially available marker for persistent or recurrent disease. The objective of this study was to determine microRNA (miRNA) expression in PTC and determine whether 1 or more miRNAs could be measured in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(178 citation statements)
references
References 40 publications
9
161
1
5
Order By: Relevance
“…Recent studies have demonstrated that some miRNAs have the potential to be used as diagnostic or prognostic markers for PTC (24,31). Combining two or three markers constitutes a more accurate approach to differentiating malignant tumors from their benign counterparts when compared with using a single biomarker (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that some miRNAs have the potential to be used as diagnostic or prognostic markers for PTC (24,31). Combining two or three markers constitutes a more accurate approach to differentiating malignant tumors from their benign counterparts when compared with using a single biomarker (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-146b appears to be a prognostic factor for PTC, as it is associated with aggressive clinicopathological features and a poor clinical outcome (37). It has also been proven to be elevated in the serum of patients with PTC and some of its target genes have been validated in thyroid cancer (38,39). MiR-146b specifically represses PAX8 and NIS, two genes essential for determining the differentiate phenotype of thyroid cancer (40).…”
Section: From Cancer Genes To Signaling and Differentiation: Toward Amentioning
confidence: 99%
“…When lesion results are interpreted as indeterminate, thyroidectomy is commonly recommended as a second surgical procedure, because indeterminate may be consistent with malignancy (Faquin and Baloch, 2010;Layfield et al, 2010). However, only 20-30% of the indeterminate lesions have a malignancy risk because up to 80% of indeterminate lesions are benign, making a significant number of surgeries potentially avoidable (Khan et al, 2013;Lee et al, 2013). A combination of other diagnostic procedures have been used to solve the problem, such as the safe, sensitive, and straightforward ultrasonography method; however, this method is only effective with suspicious thyroid nodules, and is ineffective with improving the accuracy of FNAB cytology in indeterminate lesions (Banks et al, 2008;Dean and Gharib, 2008).…”
Section: Introductionmentioning
confidence: 99%